Strengthening the Official National Discourse: The Impact of the First Pahlavi Government Institutions and Organizations - Moftakhri, Hossein; Salimi, Hossein (Journal of History Culture and Art Research, 2017)
The modern relics of Reza Shah created new organizations, including the National Art Association, Museum of Ancient Iran, Ancient Persia Center, Organization of the development of thoughts, Academy of the national language of Iranians, and National radio based on the discourse of authoritarian nationalism influenced by the German dialectic of Nazism, under the influence of the thinkers of this age. These institutions, in their turn, tried to act in line with the internalization of the discourse of the official nationalism of the modern authoritarian state and the Iranian national identity defined by that discourse focusing on antiquity, authoritarianism, love for Shah, modernization and emphasis on national language. The current paper tries to address the actions of these institutions in constructing the Iranian national identity based on the discourse of authoritarian romantic nationalism.